The Digital Generation Reaches Maturity Brave New World Wide Web. - Lichy, Jessica (Cambridge Scholars Publisher, 2022)
Based on a selection of scholarly investigations undertaken during the past decade, this book provides an outline of the changing landscape of international business and consumer behaviour, in the light of ongoing disruption caused by digital disruption and the post-pandemic conditions. It highlights a number of key factors that have shaped (and continue to do so) the business world and society as a whole. The focus here is on identifying and explaining emerging trends in the field of business management and consumer behaviour, paying attention to the influence of context (both national and co.